Membangun Minat Karir di Bank Syariah: Pengaruh Pengetahuan, Praktik Kerja, dan Lingkungan Keluarga pada Mahasiswa Perbankan Syariah IAIN Ponorogo - Mutiara, Nanda; Rizal, Fitra (CV. Civiliza Publishing, 2024)
Introduction/Main Objectives: The majority of employees in Islamic banks lack an educational background in Islamic finance, which can affect the implementation of Sharia principles. This study aims to analyze the influence of knowledge, practical work experience, and family environment on the interest of Sharia Banking students at IAIN Ponorogo in pursuing a career in Islamic banking. Research Methods: The research employed a quantitative method using primary data collected directly from respondents. Data was gathered through questionnaires and analyzed using multiple linear regression. Finding/Results: The results indicate that: (1) knowledge, practical work experience, and family environment simultaneously influence the interest of Sharia Banking students at IAIN Ponorogo in pursuing a career in Islamic banking; (2) practical work experience, when analyzed partially, does not have a significant effect on students' interest in a career in Islamic banking; (3) in contrast, knowledge and family environment have a significant impact on the career interest of Sharia Banking students at IAIN Ponorogo. Conclusion: The Sharia Banking Department at IAIN Ponorogo should enhance Sharia-based education, involve families in career activities, and optimize practical work to meet industry needs.